Engineered Stem Cells Improve Neurogenic Bladder by Overexpressing SDF-1 in a Pelvic Nerve Injury Rat Model. (18th February 2020) - Zhu, Guan Qun; Jeon, Seung Hwan; Lee, Kyu Won; Cho, Hyuk Jin; Ha, U-Syn; Hong, Sung-Hoo; Lee, Ji Youl; Kwon, Eun Bi; Kim, Hyo-Jin; Lee, Soon Min; Kim, Hey-Yon; Kim, Sae Woong; et al.
There is still a lack of sufficient research on the mechanism behind neurogenic bladder (NB) treatment. The aim of this study was to explore the effect of overexpressed stromal cell-derived factor-1 (SDF-1) secreted by engineered immortalized mesenchymal stem cells (imMSCs) on the NB. In this study, primary bone marrow mesenchymal stem cells (BM-MSCs) were transfected into immortalized upregulated SDF-1-engineered BM-MSCs (imMSCs/eSDF-1 + ) or immortalized normal SDF-1-engineered BM-MSCs (imMSCs/eSDF-1 − ). NB rats induced by bilateral pelvic nerve (PN) transection were treated with imMSCs/eSDF-1 +, imMSCs/eSDF-1 −, or sham. After a 4-week treatment, the bladder function was assessed by cystometry and voiding pattern analysis. The PN and bladder tissues were evaluated via immunostaining and western blotting analysis. We found that imMSCs/eSDF-1 + expressed higher levels of SDF-1 in vitro and in vivo. The treatment of imMSCs/eSDF-1 + improved NB and evidently stimulated the recovery of bladder wall in NB rats. The recovery of injured nerve was more effective in the NB+imMSCs/eSDF-1 + group than in other groups. High SDF-1 expression improved the levels of vascular endothelial growth factor and basic fibroblast growth factor. Apoptosis was decreased after imMSCs injection, and was detected rarely in the NB+imMSCs/eSDF-1 + group. Injection of imMSCs boosted the expression of neuronal nitric oxide synthase, p-AKT, and p-ERK in the NB+imMSCs/eSDF-1 + group than in other groups. Our findings demonstrated that overexpression of SDF-1 induced additional MSC homing to the injured tissue, which improved the NB by accelerating the restoration of injured nerve in a rat model.